The effect of blending learning using video-based blogs and the speaking skill development in students attending 1st year of bachelor at "Marcel Laniado de Wind" high school, in Machala, in the first term, 2015-2016 School year - Jaramillo Cantos, Priscila Elizabeth (2016)
The primary purpose of this project was determining the effect of Blending Learning using Video-Based Blogs and the Speaking Skill development in students attending 1ST year of bachelor at "Marcel Laniado de Wind" High School, in Machala, in the first term, 2015-2016 school year. An experimental and control group participated in this project. The control group consisted of 21 students who during this research used traditional speaking practice activities. On the other hand, the experimental group which was formed by 22 students used video-based blogs through the website Kidblog. The classes were held twice a week during a period of three months. A speaking pre-test, post-test and rubric were applied to determine the English speaking skill development in both groups.